The Extent of Knowledge, Preparedness and Perception of Telemedicine among Family Medicine Residents in Cebu City during COVID-19 - Sumanga, Kristine Joy Y.; Derecho, Clarissa Mae D. (Jurnal Biostatistik, Kependudukan, dan Informatika Kesehatan, 2023)
Telemedicine is providing healthcare services using electronic means at a distance including the diagnosis, treatment, and prevention of diseases as well as the research and evaluation, and education of healthcare providers. Its role in the time of the pandemic is vital, especially to the practice of medicine. This study is a descriptive, cross-sectional, survey research study conducted in four hospital training institutions in Cebu City. A total of 41 respondents gave their consent and were given the online survey questionnaire about the extent of knowledge, preparedness and perceptions of telemedicine. Out of the 41 respondents, 56.10% were young adults (26-30 years old), mostly females (70.73%), single (68.29%), first-year residents (43.90%), employed at a government hospital (70.73%) and are in the traditional residency pathway (82.93%). On relevant experience, 82.93% experienced telemedicine during residency, with 100% on follow-up consultations, and 95% were consulted due to infections. Respondents’ extent of knowledge was average while the extent of preparedness and perception were high. Problems with low connectivity (80.48%) were noted by most of the respondents. Resident physicians moderately understood the information about telemedicine but with a high extent of preparedness and perception. Challenges to low connectivity and handling patients’ data privacy were the major concerns met by the resident physicians in the use of telemedicine.